Epidemiological Analysis of Vaccination Strategies and Demographic Patterns In COVID-19 Cases in The Midwest Region of The United States - Butros M Dahu; Solaiman Khan; Ammar Ali Salman; Youssef Michal Andraws; Akram Abo Daken; Ahmad Aburayya (Medsci Publications, 2024)
Introduction: The study discusses the uneven impact of the COVID-19 pandemic across various demographic groups in the US, focusing on Boone County, Missouri. The aim is to identify any correlation between factors such as gender, age, ethnicity, and religious beliefs with COVID-19 infection rates over a span of 22 months (from March 15, 2020, to December 2, 2021). Methods: The research methodology involves time trend analysis graphs for each demographic group, benchmarked against significant events like vaccine launches, the introduction of the delta variant, vaccine boosters, and the arrival of the omicron variant. Results: Preliminary findings suggest that males and certain racial groups, including Black or African Americans and the "All-Other" category, exhibit higher COVID-19 positivity rates throughout these defined periods. The study also delves into unique patterns among demographic groups during various phases of the pandemic. Conclusion: Our results supported the hypothesis that males and minority races such as Black or African Americans and All-Other are more likely to have a higher COVID-19 positivity rate across our defined epochs.